Surface zooplankton size and taxonomic composition in Bowdoin Fjord, north-western Greenland: A comparison of ZooScan, OPC and microscopic analyses - Naito, Akihiro; Abe, Yoshiyuki; Matsuno, Kohei; Nishizawa, Bungo; Kanna, Naoya; Sugiyama, Shin; Yamaguchi, Atsushi (Polar Science, 2019)
In Greenland, tidewater glaciers discharge turbid subglacial freshwater into fjords, forming plumes near the calving fronts. To evaluate the effects of this discharge on the zooplankton community in the fjords, we collected sea surface zooplankton samples in Bowdoin Fjord in north-western Greenland during the summer of 2016 and made microscopic, OPC and ZooScan analyses. Within the three quantitative methods, ZooScan has advantages that can evaluate various parameters (e.g., abundance, biomass, size and taxonomic information) simultaneously and has the ability to eliminate abiotic particles, such as silt and sediment, which are abundant in samples. Based on taxonomic biomass data, the zooplankton community is clustered into three groups, which varied spatially: inner, middle and outer fjord groups. Jellyfish dominated the outer fjord group, and barnacle cypris larvae dominated the middle fjord group. For the inner fjord group, large-sized Calanus spp. and chaetognaths were abundant. Since these species are characterized with oceanic taxa, they would intrude through the deep fjord water and subsequently be upwelled through entrainment of glacially modified plume water. From the NBSS analysis on zooplankton size spectra, the steep slope of NBSS in the middle fjord community suggests that the high productivity was caused by the addition of meroplanktonic cypris larvae. journal article